2021
DOI: 10.15671/hjbc.961220
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye Tatlısularında Egzotik Yeşil Kılıçkuyruk(Xiphophorus hellerii)’nin İlk ve Lepistes (Poecilia reticulata)’nın İlave Kaydı

Abstract: C anlı doğuran poeciliidler, birkaç istisna dışında en popüler ve en çok ticareti yapılan süs balığı türleri arasında yer almaktadır. Dolayısıyla, bu türler genellikle akvaryum meraklıları tarafından kendi doğal alanlarının dışındaki doğal sulara sıklıkla taşınmaktadır. Bu çalışmada, Türkiye'nin doğusunda (38°34′ 32″K, 37°29′21″D) bir sıcaksu kaynağında iki egzotik poeciliid türü, kılıçkuyruk (Xiphophorus hellerii) ve lepistes (Poecilia reticulata) türlerinin yabani popülasyonları kaydedilmiştir. Bu, Türkiye'd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This is probably the lowest size found in introduced populations of feral P. reticulata and X. maculatus. In other sites and environments throughout Brazil and the world, the smallest reproductive size of feral guppy and southern platyfish ranged between 1.2-2.0 cm, and 1.7-2.0 cm SL respectively Andrade et al, 2008;Montag et al, 2011;Kırankaya & Ekmekçi, 2021;Luduvice & Brito, 2023). In the present study, we also found smallest females of P. reticulata and X. maculatus measuring 4.4-5.0 cm TL respectively, indicating a feralization process for both species.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is probably the lowest size found in introduced populations of feral P. reticulata and X. maculatus. In other sites and environments throughout Brazil and the world, the smallest reproductive size of feral guppy and southern platyfish ranged between 1.2-2.0 cm, and 1.7-2.0 cm SL respectively Andrade et al, 2008;Montag et al, 2011;Kırankaya & Ekmekçi, 2021;Luduvice & Brito, 2023). In the present study, we also found smallest females of P. reticulata and X. maculatus measuring 4.4-5.0 cm TL respectively, indicating a feralization process for both species.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, we also found smallest females of P. reticulata and X. maculatus measuring 4.4-5.0 cm TL respectively, indicating a feralization process for both species. Previous studies have documented that ornamental strains of guppy and southern platyfish females living in predation free environments (i.e., aquariums) are usually larger, e.g., 6.0 cm TL (Sterba, 1983), than their feral counterparts, e.g., 4.0-5.1 cm TL in P. reticulata and X. maculatus (Favilli et al, 2018;Kırankaya & Ekmekçi, 2021), likely due to selecting forces such as predation acting upon the body size (Endler, 1982;Reznick & Endler, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, non‐native species often outcompete native species for resources (Top Karakuş et al, 2021), but they may also alter local ecosystems, sometimes irreversibly (Bernery et al, 2023). According to recent studies, the number of non‐native species in the Euphrates and Tigris catchments has surpassed 30 established non‐native species (Esmaeili, 2021), continuing to increase with new introductions (Kırankaya & Ekmekçi, 2021). Since the 1950s, reservoirs across Iran have been invaded by the grass carp ( Ctenopharyngodon idella ), one of the large carps native to China (Armantrout, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Because primarily native species were targeted by the underlying surveys, the distribution of non‐native species (especially in the Euphrates catchment) remained anecdotally described. For example, C. carpio , Carassius carassius , C. gibelio and Oncorhynchus mykiss were recorded in the Atatürk Reservoir located in the Euphrates River (Bayhan, 2021), Xiphophorus hellerii and Poecilia reticulata are known for the upper Euphrates catchment (Kırankaya & Ekmekçi, 2021), H. fossilis is known to occur in the Tigris catchment (Kaya et al, 2016), and Atherina boyeri was described from the Devegeçidi Reservoir (Ünlü et al, 2017). However, these species did not occur in the collection material analysed, emphasizing the prevailing threat presented by lacking or anecdotal information on community compositions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation